Temptation and Revealed Preference - Noor, Jawwad (Econometrica, 2011)
Gul and Pesendorfer (2001) model the static behavior of an agent who ranks menus prior to the experience of temptation. This paper models the dynamic behavior of an agent whose ranking of menus itself is subject to temptation. The representation for the agent's dynamically inconsistent choice behavior views him as possessing a dynamically consistent view of what choices he “should” make (a normative preference) and being tempted by menus that contain tempting alternatives. Foundations for the model require a departure from Gul and Pesendorfer's idea that temptation creates a preference for commitment. Instead, it is hypothesized that distancing an agent from the consequences of his choices separates normative preference and temptation.